Chen’s peiyuan tang and premature ovarian failure: unveiling the mechanisms through network pharmacology - Yang, Xiao; Mao, Yi-Ming; Yao, Chong; Song, Ding-ming; He, Yi-bo; Shen, Wei (Frontiers in Pharmacology, 2024)
Premature ovarian failure (POF) is a clinical syndrome affecting women under 40, characterized by amenorrhea, elevated follicle-stimulating hormone (FSH) levels, and diminished estrogen levels, leading to significant fertility issues and increased risks of cardiovascular disease, osteoporosis, and Alzheimer's disease. Traditional Chinese Medicine (TCM), specifically Chen's Peiyuan Tang (CSPYT), offers a promising alternative to conventional hormone replacement therapy (HRT), which carries risks such as cancer. CSPYT, a compound herbal formula, has shown potential in enhancing ovarian function and mitigating autophagy in ovarian granulosa cells, crucial for follicle development and maturation. This study explores CSPYT's therapeutic mechanisms in treating POF, focusing on its modulation of autophagy through network pharmacology and transcriptomics-based analysis, predicting potential interactions and pathways. KGN cell line and rat ovarian granulosa cells were used for in vitro experiment. 4-Hydroperoxy cyclophosphamide(4-HC) stimulation was carried out for establishing the POF cell model. Q-PCR, Western Blot, Transmission electron microscopy to detect the results. Key findings indicate that CSPYT inhibits the MAPK signaling pathway, preventing autophagy overexpression and restoring ovarian granulosa cell function, presenting a multifaceted treatment potential for POF.